Distribution Transformer Capacity Planning Based On Load Characteristics According To Electric Power Requirements At The Mugarsari Campus, Siliwangi University - Azizah, Faridah Nafa; Andang, Asep; Sutisna, Sutisna (Jurnal Teknik Elektro Indonesia, 2024)
Siliwangi University is currently building a second campus in the Mugarsari Tasikmalaya area. With the construction of this second campus, it is necessary to plan the transformer capacity in accordance with the installed electrical power requirements. In terms of designing electrical installations and the need for electrical power to be installed, proper planning is needed. In this research, the distribution transformer capacity value planning has been carried out in accordance with the installed electrical power requirements by considering load characteristics, namely demand factors and diversity factors. The aim of this research is to determine the capacity of the distribution transformer along with an analysis of the distribution transformer loading so that it complies with PLN standards. The total installed load is 1,566 kVA. In this study, calculations were carried out based on load characteristics, namely diversity factors and needs factors . The distribution transformer capacity obtained by considering load characteristics is 1,220 kVA with a loading percentage of 81% . The results of the loading that have been carried out are still in accordance with the Electricity Planning Projections through the 2020 RUPTL.